1970
DOI: 10.3329/bmrcb.v34i3.1856
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of metabolic factors among the patients with essential hypertension

Abstract: The prevalence of metabolic syndrome was determined in clinic-based 1,517 hypertensive patients. All traits were present in 1.1% men and 12.8% women. Combination of different three traits were present as follows; hypertension with high triglyceride and low HDL (men 29.4% vs. women 51.8%), hypertension with high blood glucose and low HDL (men 13.5% vs. women 29.8%), hypertension with high glucose and high triglyceride (men 18.1% vs. women 18.1%), hypertension with high blood glucose and large waist (men 2.7% vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…15 On the other hand, incidence of metabolic syndrome is higher in hypertensive subjects in comparison to the general population; in a study among hypertensive patients, 31.7% had hyperglycaemia, 38.7% high waist circumference, 68.8% low high density lipoprotein (HDL) cholesterol and 55.3% high triglycerides. 17 Serum total cholesterol, triglyceride, and LDL-cholesterol were markedly raised (P < 0.001) whereas HDL-cholesterol was significantly lower (P < 0.001) in hypertensive as compared to control subjects in a study investigating serum lipid profile in hypertensive subjects. 18 Tobacco consumption is quite common in Bangladesh: prevalence is 51% for any form, 26.2% for smoking, and 31.7% for smokeless tobacco.…”
Section: Lifestyle-related Factorsmentioning
confidence: 99%
“…15 On the other hand, incidence of metabolic syndrome is higher in hypertensive subjects in comparison to the general population; in a study among hypertensive patients, 31.7% had hyperglycaemia, 38.7% high waist circumference, 68.8% low high density lipoprotein (HDL) cholesterol and 55.3% high triglycerides. 17 Serum total cholesterol, triglyceride, and LDL-cholesterol were markedly raised (P < 0.001) whereas HDL-cholesterol was significantly lower (P < 0.001) in hypertensive as compared to control subjects in a study investigating serum lipid profile in hypertensive subjects. 18 Tobacco consumption is quite common in Bangladesh: prevalence is 51% for any form, 26.2% for smoking, and 31.7% for smokeless tobacco.…”
Section: Lifestyle-related Factorsmentioning
confidence: 99%
“…Classically it used 5A strategies (ask, advise, assess, assist, and arrange) in local language (Bangla). 6,9 Between October 2004 and September 2014 a total of 259 patients registered in the hypertension clinic. They were routinely asked to come for follow up at four weeks interval.…”
mentioning
confidence: 99%
“…The higher prevalence among women may be due higher prevalence of obesity among women, and also the relatively sedentary life style of women in this part of the world, from socio cultural barriers in which women do not engage in work related physical activities. A few studies however reported equal prevalence between gender and even a male preponderance, which may be probably, due to different methodologies ( Alegria et al, 2005;Ohta et al, 2007;Badr et al, 2007;Abu et al, 2008;Fezeu et al, 2007).…”
Section: Discussionmentioning
confidence: 99%